HUBUNGAN PENDEKATAN BELAJAR DENGAN BURNOUT PADA MAHASISWA PREKLINIK FAKULTAS KEDOKTERAN UNIVERSITAS NUSA CENDANA - Susilowati, Anggi Rahmandinah; Wunguow, Herman Pieter Louis; Ratu, Kristian; Folamauk, Conrad Liab Hendricson (Cendana Medical Journal, 2026)
ABSTRACT Background: The medical school curricula is one of the most difficult curricula in the world and special attention about mental so that medical students are more susceptible to mental health problems. If medical students do not use the effective learning approach then will be difficult to adjust to academic demands, so that learning results tend to be lower and can cause stres. A long period of stres can lead to burnout. Objective : To determine the relationship between learning approach and burnout among students of the Faculty of Medicine, University of Nusa Cendana Methods: This reasearch is an observational analytic study with cross sectional design conducted on preclinical students of Faculty of Medicine, University of Nusa Cendana. The sampling technique was stratified random sampling with a sample size of 157 respondents from the 2018, 2019 dan 2020 batches. Learning approach data were obtained from filling out the ASSIST questionnaire and burnout data were abtained from filling out the CBI-S questionnaire via google form. The study was analyzed by univariate, bivariate using the coefficient contingency and multivariate using logistic regression. Result: The result of bivariate analysis with the Contingency Coefficient test obtained p value = 0,027(p<0,05) and r=0,288 Conclusion: There is a significant and weak relationship between learning approach and burnout among students of the Faculty of Medicine, University of Nusa Cendana. Key Words : learning approach, burnout, medical students